The Federal Institute of Education, Science and Technology of Mato Grosso do Sul and its contribution to the regional development of Ponta Porã and its catchment area (Research, Society and Development, 2022)
The present work is the result of a research presented in the stricto sensu graduate program in regional development and productive systems - PPGDRS of the State University of Mato Grosso do Sul. Where the contribution of the Federal Institute of Education, Science was investigated. and Mato Grosso do Sul Ponta Porã Campus Technology for the regional development of its coverage area. In this process of understanding the proposed theme, a survey was carried out on the implementation and expansion of Federal Institutes, based on Federal Law nº 11892, of December 29, 2008, which, in its wording expresses that the internalization of teaching technical aims to boost regional development. Based on this research, it can be seen that the IFMS Ponta Porã has been making efforts to get closer to the community through events and partnerships with municipalities and institutions in the region. It is also noted that professional training in the courses analyzed present good prospects for the insertion of graduates in the labor market and increase in income. It can be inferred that the institution not only serves business, utilitarian and instrumental education, but also allows for a critical, humanistic, holistic view, since through the training received at the institution, individuals are able to make choices, including that of be able to continue studies in academic life. The contributions of the IFMS of Ponta Porã to regional development occur with the training of young people and adults for the world of work, through the entry of graduates into the labor market, with the holding of scientific and cultural events in the municipality.